2011
DOI: 10.1093/hmg/ddr470
|View full text |Cite
|
Sign up to set email alerts
|

Inherited and de novo SHANK2 variants associated with autism spectrum disorder impair neuronal morphogenesis and physiology

Abstract: Mutations in the postsynaptic scaffolding gene SHANK2 have recently been identified in individuals with autism spectrum disorder (ASD) and intellectual disability. However, the cellular and physiological consequences of these mutations in neurons remain unknown. We have analyzed the functional impact caused by two inherited and one de novo SHANK2 mutations from ASD individuals (L1008_P1009dup, T1127M, R462X). Although all three variants affect spine volume and have smaller SHANK2 cluster sizes, T1127M addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
114
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 136 publications
(123 citation statements)
references
References 32 publications
9
114
0
Order By: Relevance
“…EGR3 displayed increased binding to the promoter of RhoA , a gene involved in negative regulation of dendritic structure 37 and to Actn1 , an actin-associated gene (Figure 4b). Furthermore, EGR3 binding to the Shank2 promoter, a gene involved in regulating dendritic morphology and cognitive behavior, 38 was decreased.…”
Section: Resultsmentioning
confidence: 99%
“…EGR3 displayed increased binding to the promoter of RhoA , a gene involved in negative regulation of dendritic structure 37 and to Actn1 , an actin-associated gene (Figure 4b). Furthermore, EGR3 binding to the Shank2 promoter, a gene involved in regulating dendritic morphology and cognitive behavior, 38 was decreased.…”
Section: Resultsmentioning
confidence: 99%
“…Human genetic studies have implicated SHANK2 in ASDs (5), and previous rodent experiments have reported autism-like behaviors in two different lines of Shank2 mutant mice (26,27). We conducted a series of behavioral tests to assess whether Δe24 -/-mice would display ASD-like and intellectual disability-like phenotypes similar to those associated with SHANK2 mutations in humans (4,5,39). We tested social behaviors using a sociability paradigm, which revealed no significant deficiencies in the Δe24 -/-mice of either sex ( Figure 3A and Supplemental Figure 3C).…”
Section: Shank2mentioning
confidence: 99%
“…For each sample, the system recorded position, object area and the status of defined events. Parameters assessed were total distance moved, velocity, and time in center, which was defined as the area 10 cm distant from the walls, as earlier described (Fuss et al, 2010;Berkel et al, 2012).…”
Section: Openfield Testmentioning
confidence: 99%